Study of undisturbed soil test about slope angle of the expanded-plate affecting the failure mechanism of the NT-CEP pile under vertical tension. Issue 1 (1st June 2022) - Chen, Yang; Qian, Yongmei; Hong, Guang; Jin, Yujie; Wang, Ruozhu
Abstract: In this paper, it is computer simulation studied that the influence of the slope angle of expanded-plate of the new-type concrete expanded-plate pile (the NT-CEP pile) to the uplift failure mechanism. The model piles of different slope angle are designed in undisturbed soil test, in which the effect about the bearing capacity of the NT-CEP pile and the failure behavior of the soil is analyzed, at the same time, the computer simulating analysis of finite element is assistant by the ANSYS software, to verify the test results. The innovation of this paper is mainly to test research methods, which improves and innovates the existing model test method and test equipment because of completing the test with undisturbed soil and ensuring the reliability of the test results. The research results of this paper will enrich and improve the design theory of the NT-CEP pile and play a necessary complement to the practical engineering application and a positive role in promoting the research and application of the NT-CEP pile.